PENERAPAN EDUKASI ECOENZYM SEBAGAI UPAYA PENGELOLAAN SAMPAH ORGANIK BERBASIS MASYARAKAT DI PEKON KALISARI, KABUPATEN TANGGAMUS - Sulastri Sulastri; Atmono Atmono; Debi Tetanika; Dilla Citra; Muhammad Adji Saputra; Nabila Tiyara Jesika; Valka Fajar Mahesa; Rinata Fitria Sari; Arinda Maharani Putri; Meliyanti Meliyanti; Intan Novitri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The problem of organic waste remains a major environmental issue in rural areas of Indonesia due to the lack of an integrated waste management system. This study aims to improve community understanding and skills in managing organic waste through training on the production of eco-enzyme in Pekon Kalisari, Wonosobo District, Tanggamus Regency. A qualitative descriptive approach with participatory observation was used through socialization, discussion, and hands-on demonstrations of eco-enzyme production using simple materials such as fruit peels, palm sugar, and water. The results show that the community demonstrated high enthusiasm and successfully understood the process and benefits of eco-enzyme as an environmentally friendly alternative for household waste management. Several participants committed to producing eco-enzyme independently at home. This activity effectively increased public awareness of the importance of organic waste management while strengthening collaboration between students and the local community in environmental preservation efforts. The program is expected to serve as a sustainable educational model to support community-based waste management practices.